Prevalence of Stress and coping mechanism among staff Nurses in the intensive care unit - Raja Lexshimi RG,; Saadiah Tahir,; Santhna L.P,; Md Nizam J, (Penerbit UKM, 2007)
The working environment of intensive care unit (ICU) nurses is a constant source of stress. Researchers have described ICU as a stressful environment because of the complex nature of patients’ health problems requiring an extensive use of very sophisticated technology. This study aimed to identify the prevalence of stress among staff nurses working in ICU, Hospital Universiti Kebangsaan Malaysia (HUKM), factors influencing stress and to explore the symptoms of stress experienced. This descriptive study was conducted on 67 staff nurses working in ICU, HUKM. Data was collected using selfadministered questionnaires. The questionnaires included sections on socio-demographic data, factors influencing stress and symptoms of stress experienced. Data was analysed using frequency and percentage. The Chi square test was used to examine the relationship between socio-demographic data and factors influencing stress. Findings indicated that stress symptoms were experienced by 100 per cent (n =67) of staff nurses. Knowledge, working experience, critically ill patients, and environmental factors were one of the many factors contributing to the stress experienced by the ICU nurses in HUKM. Nurses working in ICU, HUKM are found to have a high level of stress. Recommendations like encouraging ICU nurses to take up post basic ICU courses and increasing the nurses quota can reduce the prevalence of stress among ICU nurses. Hospital management has an important role to play in reducing the stress levels of nurses working in ICU as stress has an effect on job performance and quality of nursing care